Hannibal. Season one [videorecording (DVD)] - Dancy, Hugh, 1975-; Mikkelsen, Mads, 1965-; Dhavernas, Caroline; Harris, Thomas, 1940- (NBC Universal, Inc., 2013)
FBI Agent Will Graham hunts the most notorious serial killers. He is both gifted and cursed with an extraordinary ability: he can think, see, and feel like his prey. What he doesn't know is that his new partner has an extreme past. While pursuing a cannibalistic murderer, Special Agent Jack Crawford teams Graham with a psychiatrist, Dr. Hannibal Lecter. Dr. Lecter tests Graham every step of the way, playing a game all his own, while they work to unravel the mystery and catch the killer.